2015
DOI: 10.6026/97320630011261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combined herbal feed additives on methane, total gas production and rumen fermentation

Abstract: The present study was to evaluate effect of herbal feed additives on methane and total gas production during the rumen fermentation for environment and animal health concern. Different parts of the five medicinal plants were selected such as leaf and small stems of Ocimum sanctum (Tulsi), roots of Curcuma longa (Haldi), fruits of Emblica officinalis (Amla), leaves of Azadirachta indica (Neem) and leaves and small stem of Clerodendrum phlomidis (Arni) for our study. Addition of different herbal additive combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Regarding environment and animal health, the effect of functional herbs on methane production during rumen fermentation has been interestingly evaluated. For example, the lateral branches of Clerodendrum phlomidis have the potential to decrease CH 4 production with no side-effect on the ruminant health and production [9]. Saponins in some plant species were found to inhibit or suppress protozoa in the rumen and thus reduce ammonia and methane production [10].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding environment and animal health, the effect of functional herbs on methane production during rumen fermentation has been interestingly evaluated. For example, the lateral branches of Clerodendrum phlomidis have the potential to decrease CH 4 production with no side-effect on the ruminant health and production [9]. Saponins in some plant species were found to inhibit or suppress protozoa in the rumen and thus reduce ammonia and methane production [10].…”
Section: Introductionmentioning
confidence: 99%
“…Although the inclusion of SH may have a limited adverse effect on daily milk yield (from 374.94 to 413.88 g) where these differences among experimental groups may be related to that Sesban hay contains phenolic compounds such as tannins and saponin (Goel and Makkar, 2012; Chaturvedi et al 2015), which may lower CH4 production with increasing levels of SH. Phenolics, including tannins which can be mitigate CH4 production by directly inhibiting methanogenesis and protozoa and reducing fiber degradation (Patra et al, 2012;Patra, 2016).…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…Neem seed oil produces toxic effect in humans in several isolated cases and this intoxication by humans produces vomiting, acidosis, diarrhea, nausea, and encephalopathy [4,70]. These toxic effects might be due to the presence of aflatoxin and other toxic compounds found in neem oil [81]. Mechanistic investigations indicate that neem oil uncouples mitochondrial oxidative phosphorylation, thus inhibiting the respiratory chain [9,13].…”
Section: Toxicity Testing On Neem Productsmentioning
confidence: 99%
“…Various preclinical studies have been reported on the safety evaluation of different parts of neem as well as its various biologically active products [5,13,81].…”
Section: Toxicity Testing On Neem Productsmentioning
confidence: 99%
See 1 more Smart Citation